6(-4-x)=-18x

Simple and best practice solution for 6(-4-x)=-18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-4-x)=-18x equation:


Simplifying
6(-4 + -1x) = -18x
(-4 * 6 + -1x * 6) = -18x
(-24 + -6x) = -18x

Solving
-24 + -6x = -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
-24 + -6x + 18x = -18x + 18x

Combine like terms: -6x + 18x = 12x
-24 + 12x = -18x + 18x

Combine like terms: -18x + 18x = 0
-24 + 12x = 0

Add '24' to each side of the equation.
-24 + 24 + 12x = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 12x = 0 + 24
12x = 0 + 24

Combine like terms: 0 + 24 = 24
12x = 24

Divide each side by '12'.
x = 2

Simplifying
x = 2

See similar equations:

| 0.4x+3=-0.2x-0.6 | | 5x+5=3x+4+2x+1 | | x^2+bx+6.25=0 | | 90=2x+10 | | X+y=122 | | -3(4+3)=2y+3 | | 17-3=4x | | -3(q-7)=2+q-21 | | 2x+1=2(x-4) | | 3x^5/6-16=80 | | 2x+1=2(x-8) | | x-5+4x+x+x-8=360 | | 3x-7(x+6)=14 | | 2/3x=1=-1/3x-1 | | 20(-9+6)=-6(x-2) | | 4(3-z)-36=26z-6(4+5z) | | y=c(x-2) | | 4sin^2x+11sinx-3=0 | | 4(3+x)=-4-x | | 1/2(2p-12)=10p | | 12+3x=1.2-4x | | 12+3x=1.24x | | 1n-4=3n+6 | | x+100=3x+50 | | 3(a-3)+6=12 | | y=1/-1/4 | | (.33333)d-5=81 | | -d+5=4 | | -12-5[6-(2*6)]=18 | | 16x^4-7x^2-18=0 | | (1/3)d-5=81 | | -1n+-2+6=-9+8n+4 |

Equations solver categories